Ventilación dual en conejos con condiciones pulmonares heterogéneas. Evaluación del dispositivo ACRA. Estudio preliminar. - Tarragona, L. (2021)
The current COVID-19 pandemic has led to a worldwide shortage of ventilators. Ventilator sharing has been\nadvocated as an alternative to cope with this sudden increase in critically ill patients requiring ventilatory assistance. To handle this worldwide contingency, different therapeutic approaches have been proposed. This study describes the performance of a new interface called ACRA (Artificial Respirator Capability Enhancement), specifically designed to split the outflow of a ventilator into two breathing systems, overcoming several of the limitations that could arise from dual ventilation. The aim was to evaluate the capacity of the ACRA to guarantee the provision of an independent and simultaneous protective ventilation strategy in two rabbits with different pulmonary conditions. The experiment consisted of placing the ACRA device between a mechanical ventilator and two anesthetized rabbits with heterogeneous pulmonary conditions. Ventilation was performed in a pressure-controlled mode. In all phases, individual pressure values were obtained from the interface analog manometers and tidal volume values were obtained from the ventilator, which was verified with data obtained from additional flow sensors. Ventilatory and hemodynamic variables were evaluated during two hours of ventilation. In the experimental model tested, division of the ventilator outflow, independent pressure adjustments, and individual administration of tidal volume were feasible, despite the heterogeneous lung condition of the individuals tested. The interposition of the ACRA allowed the execution of a protective pulmonary ventilation and the preservation of the hemodynamic balance. Although dual ventilation has only been suggested during a serious crisis in the healthcare system, this experiment proposes the ACRA device as an alternative to expand the capacity of ventilators in emergency situations, individualizing the needs of each patient.